Developing Children’s Socio-Emotional Competencies Through Drama Pedagogy Training: An Experimental Study on Theory of Mind and Collaborative Behavior - Macarena-Paz Celume; Thalia Goldstein; Maud Besançon; Franck Zenasni (Europe's Journal of Psychology, 2020)
Drama pedagogy training (DPT) is a drama-based-pedagogy focused on socio-emotional-learning (SEL) development, over academic or artistic. This study aims to see if DPT promotes theory of mind (ToM) and collaborative behavior in 126 French children aged 9-10 years old, randomly assigned to an experimental group (DPT), either a control group for 6 weeks. Post-tests showed large effects of training on ToM, F(1, 124) = 24.36, p < .001, η² =.16, and collaborative behavior, F(1, 124) = 29.8, p < .001, η² = .19. T-test showed significant differences on ToM (t = -4.94, p < .001) and collaborative behavior (t = -5.46, p < .001), higher for DPT. Effects of type of school and grade are discussed. Results confirm the hypotheses.